Assessment of Landslide Vulnerability in Urban Areas Using GIS and Remote Sensing: A Study in Ambon City - Lasaiba, Mohammad Amin; Tetelepta, Edward Gland; Ansiska, Paisal (JURNAL GEOGRAFI, 2024)
Slope stability and land movements, commonly referred to as landslides, are natural hazards that involve the shifting of materials like soil, rock, and debris, primarily caused by the force of gravity. This research utilized both qualitative and quantitative approaches, focusing on spatial analysis by examining primary and secondary data derived from satellite imagery, observations, and pertinent institutions. Processing of the collected data using specialized software like Global Mapper 20, ArcGIS 10.8.1, and ER Mapper 8.1. The findings of this investigation disclosed that a significant portion of Ambon City, roughly 51.63% of its area, exhibited high susceptibility to landslides. Conversely, only about 16.26% of the total area demonstrated very low or low vulnerability. Similar trends were observed in urbanized regions, where the majority, around 39.01%, were classified as highly vulnerable (Z-4). In contrast, approximately 35.09% showed very low vulnerability (Z-1), and 11.89% depicted low vulnerability (Z-2). The study's findings clearly highlight a critical situation in Ambon City, where a substantial 89% of its territory, characterized by mountainous landscapes, is experiencing a markedly increased frequency of landslides. Given these concerning insights, it is absolutely essential for government authorities to engage in rigorous spatial planning. This should involve redirecting development efforts towards areas identified as safer, away from high-risk zones. Furthermore, the government must enforce and adhere to policies that not only mitigate landslide risks but also promote sustainable development, ensuring the long-term safety and resilience of Ambon City against such natural disasters.Keywords: Mapping, Landslide, Vulnerability, Build Area